Sosialisasi Pentingnya Menabung Pada Anak Usia Dini di Desa Gongsol Kecamatan Merdeka Kabupaten Karo - Mela Carisa; Adinda Wizurai Siregar; Amellya Ade Rewina Br Sibarani (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This community service activity aims to increase awareness and understanding of early childhood children regarding the importance of saving, especially in facing financial challenges in the future. This program is implemented in Gongsol Village, Merdeka District, Karo Regency, and involves children and parents as the main participants. Through an approach that includes socialization, mentoring, and evaluation, this activity focuses on developing savings habits from an early age as part of basic financial literacy. The methods used in this program include initial surveys, interviews, direct socialization, and the creation of educational media in the form of creative piggy banks to motivate children to be more enthusiastic about saving. The results of this activity show a significant increase in children's understanding of the concept of saving, its benefits, and how to do it effectively. In addition, this program also educates parents about the importance of supporting children in forming savings habits from an early age, in order to prepare them for financial challenges in the future. This socialization has been proven to be able to form a more positive mindset regarding financial management in children, teaching them discipline, responsibility, and independence in managing their pocket money. This program is also expected to be integrated into the school curriculum in the village, to strengthen the habit of saving as part of character education and financial literacy. With ongoing support from various parties, including schools and families, the habit of saving from an early age can be the foundation for the financial stability of individuals and society as a whole.